Liberalismo económico y expertos internacionales en su encuentro con América Latina. La visita del economista francés Courcelle-Seneuil a Chile, 1855-1863 - Jimena Caravaca (Nuevo mundo - Mundos Nuevos, 2019)
The article bases on the visit of the French economist Jean Gustave Courcelle-Seneuil (1813-1892) to Chile between 1855 and 1863 to analyze the early forms assumed by international economic advice and the theoretical and practical positions of the French in relation to the Chilean case. The article is based on materials produced by the French expert for the Chilean government, theoretical manuals of his authorship, publications products of his stay in Chile, and bibliography on international experts and economic missions